Nontrivial Periodic Solutions for Nonlinear Second-Order Difference Equations - Tieshan He; Yimin Lu; Youfa Lei; Fengjian Yang (Discrete Dynamics in Nature and Society)
This paper is concerned with the existence of nontrivial periodic solutions and positive periodic solutions to a nonlinear second-order difference equation. Under some conditions concerning the first positive eigenvalue of the linear equation corresponding to the nonlinear second-order equation, we establish the existence results by using the topological degree and fixed point index theories.